Spatial and temporal variability in MLT turbulence inferred from in situ and ground-based observations during the WADIS-1 sounding rocket campaign - Strelnikov, Boris; Szewczyk, Artur; Strelnikova, Irina; Latteck, Ralph; Baumgarten, Gerd; Lübken, Franz-Josef; Rapp, Markus; Fasoulas, Stefanos; Löhle, Stefan; Eberhart, Martin; Hoppe, Ulf-Peter; Dunker, Tim; et al. (Annales Geophysicae, 2017)
In summer 2013 the WADIS-1 sounding rocket campaign was conducted at the Andøya Space Center (ACS) in northern Norway (69° N, 16° E). Among other things, it addressed the question of the variability in mesosphere/lower thermosphere (MLT) turbulence, both in time and space. A unique feature of the WADIS project was multi-point turbulence sounding applying different measurement techniques including rocket-borne ionization gauges, VHF MAARSY radar, and VHF EISCAT radar near Tromsø. This allowed for horizontal variability to be observed in the turbulence field in the MLT at scales from a few to 100 km. We found that the turbulence dissipation rate, " varied in space in a wavelike manner both horizontally and in the vertical direction. This wavelike modulation reveals the same vertical wavelengths as those seen in gravity waves.